Desain Aplikasi Pelayanan Administratif berbasis Android - Muhammad Benny Chaniago; Suckma Azani; Ari Purno W; Dani Hamdani; Heri Heryono (JUMANJI (Jurnal Masyarakat Informatika Unjani), 2021)
The village administrative office in Jenggala village is one of the offices that have trouble doing services to the public, especially in making official letters. The lack of facilities in managing and making official letters applied by the people can disrupt the staff's performance and slow down the official letters' pace. Some of the problems that occur are general administrative work done manually, limited working hours at the office, public data loss previously submitted, and poor reporting. The head office does not know all messages and information presented in a certain period. The researcher aims to create an android-based administration service application to facilitate the public in making the official letters as needed. Researchers design the application to be fast, precise, and effective communication between the people and the officer. Researchers built applications to facilitate the village government in managing the reports in making official letters delivered by the citizen of Jenggala. Therefore, the application tends to provide convenience and flexibility in making official letters in Jenggala Village. Keyword: Jenggala, Android, Administration Service Application